Excelência e trabalho docente na pós-graduação em educação da Universidade Federal de Minas Gerais - Pauliane Romano Cirilo (2021)
The research developed for this thesis has as its main objective to unveil the conceptions of excellence in graduate studies assumed at different levels – international: international organizations and higher education rankings; national: Coordination for the Improvement of Higher Education Personnel (CAPES) and National Council Scientific and Technological Development (CNPq); institutional: Federal University of Minas Gerais (UFMG) and location: Graduate Program in Education (PPGE) at UFMG – and understand the implications that such meanings entail for the work of PPGE/UFMG professors The object of the study delimited here refers to the changes observed in the teaching work from the regulation of the policy of excellence postgraduate studies. The main argument is that the transformations derived from the logic of excellence deepened the competitive process of evaluation and ranking of the graduate program that increasingly demands from its professors to increase or sustain the qualification. Thus, the time frame of the study covers the period from 2004 (year of implementation of the Academic Excellence Program) to 2017 (year of the result of the last postgraduate evaluation). The analyzes carried out were supported by a critical perspective. It is understood that the theme is inserted in the context of the structural crisis of capitalism and the globalization of financial capital in which the distinction, expansion and internationalization of higher education institutions are based on their capacity, especially in the dimension of research, with the purpose of generating economic development. For this purpose, a qualitative methodology was used, developed through document analysis and field research. The data collection techniques used were: semi-structured interviews with professors from the PPGE/UFMG and survey of documentary sources. The interviews were analyzed with the support of the Nvivo software. The collected material was explored based on content analysis. Data analysis evidences the conformation of excellence as a policy promoted by the induction of the State, with a view to expanding business profits through the transformation of knowledge into raw material. In this context, excellence is supported as a matrix of quality in higher education, based on the evaluation of Graduate Programs. It is intrinsically aligned with the expansion of higher education in the privatist molds, based on managerialism and neoliberalism. The policy of excellence promotes the hierarchy and fragmentation of teachers and PPGs; deepens the process of intensification and productivity of postgraduate teaching work. The role of international organizations, especially the World Bank, is highlighted as an inducer of this conformation, through their guidelines and financing, which seek to consolidate this new rationale for higher education and the production of knowledge. Excellence is, therefore, the result of the consolidation of postgraduate studies as a level of education structured to support the country's developmentalism, whether through the training of high-level professionals, the production of raw material knowledge or the development of science, technology and innovation at the service of the market.